A study to assess proportion of the maternal near miss to maternal death in a tertiary care teaching hospital of North East India - Sarkar, Pradip; Baidya, Jahar Lal; Rakshit, Ashis Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of present study was to assess the proportion of maternal near miss and maternal death and the causes involved among patients attending obstetrics and gynaecology department of Agartala Govt. Medical College of North Eastern India. Methods: Potentially life-threatening conditions were diagnosed, and those cases which met WHO 2009 criteria for near miss were selected. Maternal mortality during the same period was also analyzed. Patient characteristics including age, parity, gestational age at admission, booked, mode of delivery, ICU admission, duration of ICU stay, total hospital stay and surgical intervention to save the life of mother were considered. Patients were categorized by final diagnosis with respect to hemorrhage, hypertension, sepsis, dystocia (direct causes) anemia, thrombocytopenia, and other medical disorders were considered as indirect causes contributing to maternal near miss and deaths. Results: The total number of live births during the study period (January 2017 to June, 2018) was 9378 and total maternal deaths were 37 with a maternal mortality ratio of 394.5/1 lakh live births. Total near miss cases were 96 with a maternal near miss ratio of 10.24/1000 live births. Maternal near miss to mortality ratio was 2.6. Of the 96 maternal near miss cases - importantly 20.8% were due to haemorrhage, 19.8% were due to hypertension, 13.5% were due to sepsis, and 11.5% were due to ruptured uterus. In maternal death group (n-37), most important causes were hypertensive (40.5%) followed by septicemia (21.6%), haemorrhage (10.8). Conclusions: Haemorrhage, hypertensive disorders and sepsis were the leading causes of near miss events as well as maternal deaths.